ANALISIS HUBUNGAN KESALAHAN, PEYIMPANGAN DAN PELANGGARAN PENGGUNA RODA DUA TERHADAP KESELAMATAN BERKENDARA - Ammar Fadhil; Renni Anggraini; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
Population growth is increasing rapidly every year. The increase that occurs will affect the need for transportation in order to make it easier for humans to meet the needs of life and carry out daily activities. The motorcycle is one of the modes of transportation in Aceh that is greatly increasing. The increase in motorcycle ownership is not matched by increased awareness of traffic safety by road users, which will have an impact on the increase in the number of accidents, the human factor has a high contribution effect on traffic accidents. WHO (2018) reports the number of deaths based on road users in Indonesia, where 74% of a number of deaths are contributed by motorcycle riders. This study aims to identify personal characteristics, unsafe and aggressive-related driving behavior, and the feeling of anxiety towards traffic safety for motorcycle users in Banda Aceh City. The data used in this research will be collected in Banda Aceh and Aceh Besar using the Driving Behavior Inventory (DBI) instrument through the “self-reporting” approach by using Google form online questionnaire given to 300 respondents. Multivariate SEM CFA model to analyze the causal relationship between personal characteristics, unsafe and aggressive driving behavior, and the feeling of anxiety towards traffic safety. The results showed that the errors had a significant effect of 0,146 on safety and violation had a significant effect of 0,453 on driving safety. Based on the result, it can be concluded that the driving errors and violations factor committed while driving has a significant effect on unsafe behavior. Driving safety is the most determining factor for unsafe driving behavior. This shows that unsafe behavior by motorcyclists is one of the factors causing motorcycle accidents in Banda Aceh and Aceh Besar.